Pluralism and individualization in the Argentine religious field: Challenges for Catholicism in the perspective of society and politics - Mallimaci, Fortunato Horacio (2015)
This article analyses the changes in the modern Argentine religious field. Based upon statistical studies on beliefs and religious attitudes, we describe the consequences of secularization in Argentine society, the way in which people believe and practice religion, the changes in religious identification, the religious diversification process and the way in which the religious practices’ and beliefs’ level of institutionalization have been decreasing. In this framework, we trace the development of the complex relationship between the State, the politics and the Catholic institution. We focus particularly on Catholicism because it is the most prominently public religion in Argentina, the most powerful and the most influent on the State and political arenas.